2021
DOI: 10.3390/foods10112778
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Sarcocornia Species: Ethnopharmacology, Nutritional Properties, Phytochemistry, Biological Activities and Propagation

Abstract: Sarcocornia A. J. Scott is a halophytic edible succulent plant belonging to the Amaranthaceae family. To date, the genus includes 28 species distributed worldwide in saline environments, usually salt marshes. Sarcocornia (Scott) is similar to Salicornia (L.), which has a recognized commercial value in morphological and taxonomical traits. Species of both genera are commonly named samphire or glassworts in Europe, and their fleshy shoots are commercialized under their traditional names. Due to their nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 109 publications
2
27
1
1
Order By: Relevance
“…In this study, the daily saline excretion between groups was also compared at the two assessment times, and through its results we can observe a significant reduction in the levels of sodium in the urine of individuals belonging to the intervention group. Several studies have indicated that Sarcocornia is a halophyte rich in minerals such as magnesium and potassium, which improve the body’s sodium excretion, thus supporting the data obtained in the present investigation [ 18 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the daily saline excretion between groups was also compared at the two assessment times, and through its results we can observe a significant reduction in the levels of sodium in the urine of individuals belonging to the intervention group. Several studies have indicated that Sarcocornia is a halophyte rich in minerals such as magnesium and potassium, which improve the body’s sodium excretion, thus supporting the data obtained in the present investigation [ 18 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Halophyte plants, such as Salicornia and Sarcocornia, prove to be a promising substitute, given that they are plants with antihypertensive characteristics [ 15 , 35 ]. Their high content of minerals such as potassium and magnesium favors saline excretion, reducing the negative effects of sodium on the cardiovascular system and the human body in general [ 18 , 22 , 35 ]. These plants are part of the native Portuguese flora and grow in abundance in coastal salt pans, which gives them a salty taste favorable to the adaptation of the palate [ 7 , 16 , 17 , 18 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their young, fleshy tips are edible and commercialised with the name of "samphire", "sea asparagus", "pickleweed", or "poor man's asparagus" [20]. Thanks to the crunchy texture and salty taste, their succulent shoots are highly appreciated in gourmet cuisine [21][22][23]. Moreover, they are a good source of fibre, antioxidants, and anti-inflammatory metabolites, such as vitamin C and polyphenolic compounds, making them an ideal nutraceutical supplement [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the crunchy texture and salty taste, their succulent shoots are highly appreciated in gourmet cuisine [21][22][23]. Moreover, they are a good source of fibre, antioxidants, and anti-inflammatory metabolites, such as vitamin C and polyphenolic compounds, making them an ideal nutraceutical supplement [23,24]. These species are also appreciated as oil-seed crops.…”
Section: Introductionmentioning
confidence: 99%